Effects of roller skiing and running exercises at the same intensities on fat and carbohydrate metabolism in cross country skiers - Cetin, E.; Atepoolu, U.; Yarym, Y. (Abstractbook. The First International Low Lands Congress on Science and Skiing, Brussels, October 11th, 2008)
The purpose of this investigation was to determine the effects of roller ski and running exercises on Energy Output, MET, Fat and carbohydrate metabolism of cross- country skiers.